PSYCHOLOGICAL MECHANISMS OF STUDENTS' ADAPTATION TO THE LEARNING PROCESS: THEORETICAL AND PRACTICAL ANALYSIS - Piraliyev Omiljon Kabilovich (International Journal of Literature and Language Studies, 2026)
This article examines the theoretical and practical aspects of the adaptation phenomenon in psychology. It analyzes the processes of human adjustment to changing environmental conditions, including physiological, psychological, and social forms of adaptation, as well as cognitive, emotional, and behavioral components. The study discusses major research methods of adaptation processes, including experimental, psychodiagnostic, longitudinal, and neuropsychological approaches. The influence of individual characteristics, social environment, and cultural factors on adaptation is also analyzed. The article highlights the practical importance of adaptation research in clinical psychology, education, and social integration, and identifies promising directions for future studies.